Efficacy of elobixibat as bowel preparation agent for colonoscopy: Prospective, randomized, multi‐center study. Issue 1 (24th May 2021) - Yamaguchi, Daisuke; Hidaka, Hidenori; Matsunaga, Takuya; Akutagawa, Takashi; Tanaka, Yuichiro; Jubashi, Amane; Takeuchi, Yuki; Tsuruoka, Nanae; Sakata, Yasuhisa; Miyahara, Koichi; Tominaga, Naoyuki; Kawakubo, Hiroharu; et al.
Abstract : Background and Aim: Elobixibat is a novel ileal bile acid transporter inhibitor. This study aimed to compare the efficacy, tolerability, and safety of the combination of elobixibat and 1 L of polyethylene glycol formulation containing ascorbic acid (PEG‐Asc) solution versus the combination of sodium picosulfate and 1‐L PEG‐Asc solution as bowel preparation for colonoscopy. Methods: This multi‐center, randomized, observer‐blinded, non‐inferiority study recruited 210 outpatients who were assigned to either the elobixibat plus 1‐L PEG‐Asc group (group A) or the sodium picosulfate plus 1‐L PEG‐Asc group (group B). The quality of the bowel cleansing level was assessed by the Boston Bowel Preparation Scale (BBPS) and compared the bowel cleansing level between the groups. Data regarding bowel preparation time, patients' tolerability, and adverse events were also analyzed. Results: Data for 196 patients (99 in group A and 97 in group B) were analyzed finally. BBPS was comparable between group A and B (8.3 ± 0.9 vs. 8.3 ± 0.7; P = 0.88). Consequently, the adequate bowel preparation rate in groups A and B was 95.0% and 99.0%, respectively (−4.0%, 95% CI −9.3 to 1.5). Bowel preparation time in group A was similar to that in group B (348.2 ± 79.8 min vs. 330.8 ± 82.5 min; P = 0.13), whereas, sleep disturbance was significantly less frequent in group A than in group B (10.2% vs. 22.7%; P = 0.02). Conclusions: The combination of elobixibat and 1‐L PEG‐Asc can be considered an alternative bowel preparation for colonoscopy considering the equivalent bowel cleansing effect and less frequent sleep disturbance. The Japan Registry of Clinical Trials (jRCTs41180026).